CaII Binding Regulates and Dominates the Reactivity of a Transition-Metal-Ion-Dependent Diesterase from Mycobacterium tuberculosis - Pedroso, Marcelo M.; Larrabee, James A.; Ely, Fernanda; Gwee, Shuhui E.; Mitić, Nataša; Ollis, David L.; Gahan, Lawrence R.; Schenk, Gerhard (Chemistry : a European journal, 2016)
The diesterase Rv0805 from Mycobacterium tuberculosis is a dinuclear metallohydrolase that plays an important role in signal transduction by controlling the intracellular levels of cyclic nucleotides. As Rv0805 is essential for mycobacterial growth it is a promising new target for the development of chemotherapeutics to treat tuberculosis. The in vivo metal‐ion composition of Rv0805 is subject to debate. Here, we demonstrate that the active site accommodates two divalent transition metal ions with binding affinities ranging from approximately 50 nm for MnII to about 600 nm for ZnII. In contrast, the enzyme GpdQ from Enterobacter aerogenes, despite having a coordination sphere identical to that of Rv0805, binds only one metal ion in the absence of substrate, thus demonstrating the significance of the outer sphere to modulate metal‐ion binding and enzymatic reactivity. CaII also binds tightly to Rv0805 (Kd≈40 nm), but kinetic, calorimetric, and spectroscopic data indicate that two CaII ions bind at a site different from the dinuclear transition‐metal‐ion binding site. CaII acts as an activator of the enzymatic activity but is able to promote the hydrolysis of substrates even in the absence of transition‐metal ions, thus providing an effective strategy for the regulation of the enzymatic activity. A question of calcium: The metallohydrolase Rv0805 from Mycobacterium tuberculosis is an emerging target for chemotherapeutics to treat tuberculosis. The enzyme has two distinct metal‐ion binding sites, one for transition‐metal ions (see figure) and one for the regulatory CaII. CaII dominates the catalytic properties of this enzyme, promoting catalysis even in the absence of the transition‐metal ions.